Qualifying Dispersion and Distribution of Carbon Nanotubes in Polyamide Matrix during Melt-Mixing by Flow Simulation. Issue 5 (June 2015) - Loux, C.; Prashantha, K.; Roger, F.; Lacrampe, M.F.; Krawczak, P.
This work aims at numerically simulating the flow of nanocomposites in a twin-screw mixer so as to develop a prediction tool of nanofiller dispersion and distribution in a polymer matrix during processing. The rheological behaviour of polyamide 6 / carbon nanotubes blends (PA6/MWCNT) containing from 1 to 5 wt.% of MWCNT was investigated over a large range of shear rates (0.1 to 100 s −1 ) and temperatures (230 to 245 °C). The macroscopic dispersion of the nanotubes was assessed by dynamic rheometry. Viscosity laws of the nanocomposites were characterized and implemented in a finite element software package to compute the velocity, pressure and temperature fields during the mixing process. A good agreement was founded between the calculated and measured torques. The dispersive and distributive capability of the flow was numerically evaluated and compared to the nanotubes dispersion quality experimentally qualified by oscillatory rheometry. Experimental and numerical results are complementary and allow better understanding the mixing capability of the twin-screw mixer used to compound nanocomposites.